The dynamics of South Korea's relationship with Asia-Pacific - Norma Mansor; Keum, Hyum Kim; Md. Nasrudin Md. Akhir (Penerbit Universiti Malaya, 2016)
This book presents the dynamism of South Korea's relationship with Asia-Pacific. The chapters feature contemporary issues and topics that introduces the reader to perspectives behind fundamental differences betweeen South Korea and some of its partners, while underscoring the strong economic and trade ties between them